1998
DOI: 10.1136/jnnp.65.4.555
|View full text |Cite
|
Sign up to set email alerts
|

Autism and visual agnosia in a child with right occipital lobectomy

Abstract: Objectives-Autistic disorder is a developmental handicap with an unknown neurological basis. Current neuropsychological models for autism suggest an abnormal construction of visual perceptual representation or a deficit in executive functions. These models predict cerebral lesions in the temporo-occipital or frontal regions of autistic patients. The present study aimed at studying the presence of symptoms of autism and visual agnosia in a 13 year old girl who had a right temporo-occipital cortical dysplasia th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
1
6

Year Published

2001
2001
2015
2015

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(29 citation statements)
references
References 49 publications
0
22
1
6
Order By: Relevance
“…The potential relevance of visual perception and in particular face processing skills to social behavior is suggested by reports of SDD-like features in patients with childhood-onset prosopagnosia, 2-5 visual loss, [6][7][8][9][10][11] and apperceptive visual agnosia. 12,13 On the other hand, others argue that, even without a primary perceptual deficit, the presence of an SDD may impair the acquisition of normal face expertise during childhood. [14][15][16][17] Since the ability to discriminate subtle differences between faces develops during childhood and requires exposure and interest, 18 the development of this perceptual skill may be hampered by a social apathy that may extend to the avoidance of looking at faces.…”
Section: Discussionmentioning
confidence: 99%
“…The potential relevance of visual perception and in particular face processing skills to social behavior is suggested by reports of SDD-like features in patients with childhood-onset prosopagnosia, 2-5 visual loss, [6][7][8][9][10][11] and apperceptive visual agnosia. 12,13 On the other hand, others argue that, even without a primary perceptual deficit, the presence of an SDD may impair the acquisition of normal face expertise during childhood. [14][15][16][17] Since the ability to discriminate subtle differences between faces develops during childhood and requires exposure and interest, 18 the development of this perceptual skill may be hampered by a social apathy that may extend to the avoidance of looking at faces.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier work by Metz (1967) reported that children with ASD showed preference for much higher levels of sound than children with a learning disability. Frankel, Freeman, Ritvo, Chikamin, and Carr (1976) found that for children with ASD, specific frequencies of flickering light had reinforcement value but did not for non-ASD children, whilst specific visual agnosias have also been associated with people with ASD (Jambaque, Mottron, Ponsot, & Chiron, 1998). Overall, abnormalities have been described in all main five sensory modalities as well as kinaesthetic and proprioceptive sensation.…”
Section: Introductionmentioning
confidence: 94%
“…Reorganization of the cortico-cortical connections after early lesions has been demonstrated in cats (Caminiti & Innocenti, 1981;MacNeil et al, 1997), and was suggested as the likely mechanism underlying the cortical plasticity seen by Baseler et ai. (1999 (Warrington & James, 1988;Kartsounis & Warrington, 1991;De Renzi & Lucchinelli, 1993;Jambaqu6 et al, 1998), suggesting that the occipital region of the right hemisphere is specialized for figure integration and figure-ground discrimination. Although severe agnosia has also been reported in one case of bilateral occipital lesion, more severe on the left (Shelton et al, 1994), the more severe lesion of the right occipital lobe in FJ could explain his inferior functional recovery.…”
Section: Eegmentioning
confidence: 99%